Dynamics of the long-term distribution of precipitation in the eastern regions of Kazakhstan (Journal of Geography and Environmental Management, 2020)
Precipitation is the most variable meteorological phenomenon in time and space. The study of the regime of long-term fluctuations of precipitation is one of the most important problems. Spatial heterogeneity of precipitation was considered by many authors. The heterogeneity of the precipitation field is determined by the combined influence of large-scale atmospheric processes and the nature of the underlying surface, especially the complex relief. These factors determine the conditions for the distribution of precipitation acting in close interconnection in space and time. The article discusses the dynamics of the long-term distribution of precipitation in the eastern regions of Kazakhstan. A feature of the climatic distribution of precipitation was described, factors influencing the climatic distribution were identified, and the conditions for repetition and macroscopic exposure in the most humid and scarce periods were determined. Also, the matrix of paired correlation coefficients was determined during periods of abnormal humidity and deficit. The article describes the features of the climatic distribution of precipitation in the eastern part of Kazakhstan. The factors affecting the climatic distribution of precipitation are presented, and the recurrence and macro circulation of excessively wet and deficient periods are considered. The matrix of paired correlation coefficients in abnormally wet and deficient periods has been determined. Mathematical, statistical analyzes and methods of climatic variations were widely used in meteorology to analyze the dynamics of precipitation. During the study period 1930-2017 the annual precipitation at Semey, Oskemen, Aygoz, Zaisan stations in the eastern regions of Kazakhstan decreased by about 8–20 mm. The greatest amount of precipitation was observed in summer (428 mm), while the smallest amount was observed in January and February (7–13 % of the annual norm). In the cold season the amount of precipitation was below 55 % of the average annual norm, and the amount of precipitation in a wet year is 50% lower than the annual norm. The season of cold and wet weather began in East Kazakhstan in the 1940s, and rainfall over the year increased by more than 60 %. In 1936-1980 in East Kazakhstan there was a decrease in form W, an increase in forms C, E. In the period 1981-2008. an increase in the frequency of form III and a decrease in forms C, E increased the amount of precipitation at Semey station, reduced the amount of precipitation at Ayagoz station, and led to a uniform distribution of precipitation at Oskemen and Zaisan stations.
Keywords: precipitation anomaly, trend line, perennial precipitation rates, pair correlation, matrix, circulation forms